We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
452
1
avatar+108 

Simplify \(^{(x^{25})^{-6}}/_{(x^{-3})^{48}}\).

The power of \(x\) in the simplified expression is \(\boxed{\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\downarrow}\).

 

\(\boxed{\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\downarrow}\\ \boxed{-2\text{ }\text{ }\text{ }\text{ }\text{ }\text{ }\\ -6\\ -23\\ -26}\)

 Jan 24, 2018

Best Answer 

 #1
avatar
0

Simplify the following:

1/((x^25)^6 (x^(-3))^48)

 

For all positive integer exponents (a^n)^m = a^(m n). Apply this to (x^(-3))^48.

Multiply exponents. (x^(-3))^48 = x^(-3×48):

1/((x^25)^6 x^(-3×48))

 

Multiply -3 and 48 together.

-3×48 = -144:

1/((x^25)^6 x^(-144))

 

For all positive integer exponents (a^n)^m = a^(m n). Apply this to (x^25)^6.

Multiply exponents. (x^25)^6 = x^(25×6):

1/(x^(25×6)/x^144)

 

Multiply 25 and 6 together.

25×6 = 150:

1/(x^150/x^144)

 

Write 1/(x^150/x^144) as a single fraction.

Multiply the numerator of 1/(x^150/x^144) by the reciprocal of the denominator. 1/(x^150/x^144) = (1 x^144)/x^150:

x^144/x^150

 

For all exponents, a^n/a^m = a^(n - m). Apply this to x^144/x^150.

Combine powers. x^144/x^150 = x^(144 - 150):

x^(144 - 150)

Evaluate 144 - 150.

144 - 150 = -6:

 

x^(-6)

 Jan 24, 2018
 #1
avatar
0
Best Answer

Simplify the following:

1/((x^25)^6 (x^(-3))^48)

 

For all positive integer exponents (a^n)^m = a^(m n). Apply this to (x^(-3))^48.

Multiply exponents. (x^(-3))^48 = x^(-3×48):

1/((x^25)^6 x^(-3×48))

 

Multiply -3 and 48 together.

-3×48 = -144:

1/((x^25)^6 x^(-144))

 

For all positive integer exponents (a^n)^m = a^(m n). Apply this to (x^25)^6.

Multiply exponents. (x^25)^6 = x^(25×6):

1/(x^(25×6)/x^144)

 

Multiply 25 and 6 together.

25×6 = 150:

1/(x^150/x^144)

 

Write 1/(x^150/x^144) as a single fraction.

Multiply the numerator of 1/(x^150/x^144) by the reciprocal of the denominator. 1/(x^150/x^144) = (1 x^144)/x^150:

x^144/x^150

 

For all exponents, a^n/a^m = a^(n - m). Apply this to x^144/x^150.

Combine powers. x^144/x^150 = x^(144 - 150):

x^(144 - 150)

Evaluate 144 - 150.

144 - 150 = -6:

 

x^(-6)

Guest Jan 24, 2018

29 Online Users

avatar